Aseneth of Egypt : the composition of a Jewish narrative - Ahearne-Kroll, Patricia D. (Early Judaism and its literature ;, 2020)
"Aseneth of Egypt examines texts of Joseph and Aseneth to propose a base storyline that can be used to locate the story's origin. Patricia D. Ahearne-Kroll contextualizes the story of Joseph and Aseneth in Hellenistic Egypt by demonstrating how the base storyline reflects the literary impulse of Greek-speaking Jewish writers to redescribe their identity in Egypt, Ptolemaic strategies of legitimation of power, and Judean connections to the land of Egypt"--